Situating the (Un)Common Landscapes of Shared Futures: Developing Speculation as a Co-Design Framework of Cognitive Apprenticeship to Empower Diverse Stakeholders and Contest Bias - Ryan Pescatore Frisk; Catelijne van Middelkoop (Research and Advances in Education, 2023)
This article discusses the development of a framework within five primary cases that explore collaborations with local municipalities, corporations, organizations, various stakeholders, and educational institutions. It reviews the progression of speculation, from a pragmatic response to immediate educational demands modeling critical and experimental approaches from professional practice, toward an approach to cognitive apprenticeship (CA) (Collins et al., 1987), foregrounding digital and material discourse as a post-disciplinary externalization of cognition within situated practice (Brown et al., 1989). Speculation is developed as an operative tool or a structured operation within the design process, linking critical research components to material realities and potential futures. This approach reflects a decentralization or distribution of developmental influence and responsibility from a relatively isolated or compartmentalized linear system with strong biases toward internal, centralized knowledge to a network directly engaged with research perspectives, sociotechnical systems, situated knowledges, and practices in everyday life. Through CA techniques, including distributed scaffolding (Puntambekar, 1997), and activity sequencing (Tharp, 1993; Dennen, 2000), an iterative approach to ethnomethodological variation influenced foundational metacognitive development exemplified by higher-level progression of learning trajectories in the case studies, both inside and outside of ‘the school,’ addressing broad variation in participant competencies and substantial participant groups (up to 460). We argue that at the core of this utility is the flexibility to embrace complexity and address ongoing change while still situating foundational themes and competencies (including critical approaches to knowledge sources, participatory processes, and projected futures) as necessary components in a logical, ethical, understandable, and exploratory framework.